Studi Kasus: Asuhan Keperawatan Pada Klien Isolasi Sosial Pasca Pasung - Muhammad Fadly; Giur Hargiana (Faletehan Health Journal, 2018)
Social isolation is characterized by decline or loss inability to interact with others. This paper aimed to analyze the nursing care of social isolation on Mr. P with schizophrenia paranoid. The nursing care process is based on the standard of generalist nursing care which provided for six days from May 7th throughout 12th 2018 on Mr. P aged 32 years male. Main nursing problem was social isolation. Nursing intervention was emphasized on client’s ability to establish mutual relationship and improve client’s communication skills gradually. Nursing interventions affected client positively as manifested gy decreased signs and symptoms of social isolation on the cognitive, affective, physiological and social aspects, but there had not been a decline in behavioral aspects. Client’s barriers in establishing relationship with nurses were internal factors in which clients had negative judgments about themselves, others and the environment and external factors where clients considered the nurse as a threatening stressor. Nursing care follow-up plans are expected to be maximized for individually, family, group and community.